Validity of the General Meeting of Shareholders after the Expiration of the Term of Office of the Board of Directors and Board of Commissioners - Nirahua, Sabrina Daniella; Kuahaty, Sarah Selfina (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2025)
..The General Meeting of Shareholders is one of the organs of the company that has other authorities where this authority cannot be given to the Board of Directors or Commissioners. The purpose of this research is to review and explain the mechanism for the implementation of the General Meeting of Shareholders by the Shareholders in ensuring the validity of the actions taken when the board of directors and the board of commissioners have ended their term of office and to review and elaborate on the binding power of the appointment of the board of directors and board of commissioners without the consent of the shareholders. The method used is normative juridical with Case Approach, Conceptual Approach, and uses primary, secondary and tertiary legal materials. The results of this study show that the mechanism for the implementation of the General Meeting of Shareholders by the Shareholders in ensuring the validity of the actions taken if the board of directors and the board of commissioners have ended their term of office, if the General Meeting of Shareholders is held wit the permission of the court, then other shareholders can attend the General Meeting of Shareholders aforementioned. Then the appointment of the board of directors and the board of commissioners without the consent of the shareholders and not appointed through the appropriate General Meeting of Shareholders is invalid and null and void for the sake of law so that it does not have binding force.